Nonlinear Topological Photonic Insulator in Synthetic Space. Issue 11 (19th September 2022) - Wu, Erjie; Li, Guangzhen; Yu, Danying; Wang, Luojia; Yuan, Luqi; Chen, Xianfeng
Abstract: As an emerging field, nonlinear topological photonics attracts great attention nowadays, where pioneering works show interesting phenomena including topological edge solitons and nonlinearity‐induced coupling of light into topological edge states. In this work, the nonlinear effects in a photonic topological insulator in the synthetic space including the frequency axis of light, in a ring resonant array under dynamic modulations are studied, where the four‐wave mixing nonlinear process is included. Such nonlinear process not only induces local interactions, but also creates long‐range interactions in the frequency dimension. These results show destruction on topologically protected edge states when the nonlinear effects are increasing. Moreover, it also breaks the symmetry in the synthetic space as well as the band structure, which reflects different propagation behaviors for the different input sources with positive and negative frequency shifts and exhibits short‐time robustness in weak nonlinear cases. This work hence explores the role of nonlinear effects in affecting the edge modes in the synthetic space, which may be useful in quantum many‐body simulations and find possible applications in information processing. Abstract : Nonlinear topological photonics attracts great interest and is rarely explored in the synthetic space. This work studies the role of nonlinear effects in affecting the edge modes in a photonic topological insulator including the frequency axis of light, which may be useful in the future exploring many‐body physics in synthetic space.